Genetic polymorphism of xenobiotic metabolizing enzymes in autoimmune connective tissue diseases - Barańska, Małgorzata; Skrętkowicz, Jadwiga (Dermatology Review/Przegląd Dermatologiczny, 2011)
Autoimmune connective tissue diseases are a clinically diverse group of chronic diseases, often serious in their consequences. Their pathogenesis is connected with the influence of environmental factors depending on individual genetic predisposition, among others, on detoxification enzymes. Genetic differences in the regulation, expression and activity of genes encoding phase I and phase II drug-metabolizing enzymes can be crucial factors in defining autoimmune disease susceptibility. In this review, current knowledge about polymorphism in several of these genes is summarized.